Thymoglobulin vs. ATG-Fresenius as Induction Therapy in Kidney Transplantation: A Bayesian Network Meta-Analysis of Randomized Controlled Trials - Song, Turun; Yin, Saifu; Li, Xingxing; Jiang, Yamei; Lin, Tao (Frontiers in Immunology, 2020)
Background: Thymoglobulin (THG) and antithymocyte globulin-Fresenius (ATG-F) have not been compared directly as induction therapies in kidney transplantation. Materials and Methods: We performed a Bayesian network meta-analysis to compare THG with ATG-F by pooling direct and indirect evidence. Surface under the cumulative ranking curve (SUCRA) values were used to compare the superiority of one method over the other. Results: A total of 27 randomized controlled trials (RCT) were eligible for the network meta-analysis. Efficacy endpoints, as well as safety indicators, were statistically comparable. THG seemed inferior to ATG-F in treating delayed graft function (odds ratio [OR]: 1.27; SUCRA: 78% versus 58%), preventing patient deaths (OR: 2.78; SUCRA: 83% versus 34%), and preventing graft loss (OR: 1.40; SUCRA: 83% versus 59%) but superior to ATG-F in preventing biopsy-proven acute rejection (BPAR; OR: 0.59; SUCRA: 78% versus 39%) and steroid-resistant BPAR (OR: 0.61; SUCRA: 76% versus 49%) within the first year. THG was less effective than ATG-F against infection (OR: 1.49, SUCRA: 79% versus 54%), cytomegalovirus infection (OR: 1.04; SUCRA: 40% versus 37%), de novo diabetes (OR: 1.10; SUCRA: 90% versus 30%), and malignancy (OR: 8.40; SUCRA: 89% versus 6%). A subgroup analysis of patients at high risk for immunologic complications revealed similar results, but THG performed better for graft loss (OR: 0.82; SUCRA: 68% versus 54%). Conclusion: ATG-F seemed more effective than THG in improving the short-term kidney transplantation outcomes.